2021
DOI: 10.54771/bsj.v3i3.327
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Tingkat Pengetahuan Tentang Gizi Terhadap Kejadian Kekurangan Energi Kronik (Kek) Pada Ibu Hamil

Abstract: Kekurangan Energi Kronik (KEK) pada ibu hamil merupakan masalah yang masih terjadi sampai saat ini. Kekurangan energi kronik pada ibu hamil dapat berdampak bagi kesehatan ibu selama kehamilan, persalinan dan kondisi kesehatan anak yang akan dilahirkan. Tujuan dari penelitian ini adalah untuk mengetahui Hubungan Tingkat Pengetahuan Tentang Gizi Terhadap Kejadian Kekurangan Energi Kronik (KEK) Pada Ibu Hamil di Puskesmas Kecamatan Matraman Jakarta Timur. Penelitian ini menggunakan desain deskriptif korelasi deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…According to the chi-square test results, there is a substantial association between pregnant women's awareness of CED and p-value = 0.0002. These findings are consistent with the work of Diningsih et al [12] discovering an IP-value of 0.000-0.05 between the number of expectant mothers who received nutritional education and the prevalence of CED at the Matraman Health Center [12], [13].…”
Section: Resultssupporting
confidence: 92%
“…According to the chi-square test results, there is a substantial association between pregnant women's awareness of CED and p-value = 0.0002. These findings are consistent with the work of Diningsih et al [12] discovering an IP-value of 0.000-0.05 between the number of expectant mothers who received nutritional education and the prevalence of CED at the Matraman Health Center [12], [13].…”
Section: Resultssupporting
confidence: 92%
“…This study obtained results consistent with previous research conducted by Retni (2021) and Diningsih et al (2021), that the level of maternal knowledge about high-risk pregnancy is significantly related to the incidence of chronic energy deficiency in pregnant women. The incidence of chronic energy deficiency in pregnant women is a complex problem that requires interprofessional collaboration between health workers.…”
Section: The Effect Of Maternal Knowledge On Chronic Energy Deficienc...supporting
confidence: 92%
“…16 The results of this study were also in accordance the results from a study by Rika et al ( 2021) on the relationship between knowledge about nutrition and CED in pregnancy. 17 Aulia et al (2020) in their study on the relationship between knowledge of nutrition, food availability and intake with CED incidence also found a significant relationship between those variables. 18 In this research, it was identified that a subset of pregnant women exhibits suboptimal knowledge about nutrition during pregnancy.…”
Section: Knowledgementioning
confidence: 91%